Polycyclic Aromatic Hydrocarbons from Waste Incineration - Prakash, Vinit (My University, 2009)
This thesis reports the emissions of total 16, 2A and 2B Polycyclic Aromatic Hydrocarbons (PAHs) from the incineration of biomedical waste (BMW)/ industrial hazardous waste (HW) and the effects of combustion parameters (temperature and airflow rate) on their emissions in a specially designed laboratory scale vertical quart tube incinerator. The investigation of management practices followed by ten hospitals, a common biomedical waste treatment facility and two largest acrylic fiber producing industries of India has been under taken with a view to study emerging scenario of biomedical/ hazardous waste management. Waste samples were collected from Govt. Rajendra hospital, Patiala (blood contaminated blood bag and blood contaminated cotton) and Indian Acrylics limited, Sangrur (acrylic waste solution and cellulose waste filter). Vertical quartz tube incinerator was designed and fabricated for study of PAHs emissions in the laboratory. The collected samples were incinerated at different temperatures and air flow rates in the laboratory scale incinerator. Studies on Blood contaminated blood bag, Blood contaminated cotton, Acrylic waste solution and Cellulose waste filter has shown that there is no definite trend on PAHs distribution with combustion temperature and airflow rate. Similar findings were also reported by Mastral et al. (1999) on PAHs emissions from coal atmospheric fluidized bed combustion in the pilot scale study. The effect of temperature and airflow rate towards sum of 2A and 2B PAHs has been studied on the collected samples. Blood contaminated blood bag showed lower values of 2A and 2B PAHs at 700ºC or between 900-1000ºC with air flow rate of 1-4 L min-1. Blood contaminated cotton showed the lower values of sum of 2A and 2B PAHs at 700-800ºC with airflow rate of 1-4 L min-1. Acrylic waste solution showed the sum total of 2A and 2B PAHs to be lowest at 700-900ºC with airflow rate of 2-4 Lmin-1. Cellulose waste filter showed the sum total of 2A and 2B PAHs to be less at 700-900ºC with airflow rate of 1-2 L min-1. There has been increase in number of hospitals/ industries resulting into increase in BMW/ HW. The management of these waste become significant due to risks associated with the health of individuals. Ministry of Environment and Forest Government of India has made BMW/ HW (Management & Handling) Rules. A case study approach has been used for an in-depth analysis of BMW/ HW management practices. There are 2382 and 181 health care facilities in Punjab and Patiala district and the BMW generated is 6483.76 and 424.3 Kg day-1 respectively during 2007. 98% of the BMW waste is treated in Punjab according to BMW management rules. 16% of health care facilities violated these rules and 78% health care facilities utilize common BMW treatment facilities for disposal of waste. The hospitals of Patiala district under study supply their BMW to common BMW treatment facilities whereas Post Graduate Institute - Medical Education and Research has its own incinerator for treatment of BMW. These health care facilities are found to obey BMW (Management & Handling) Rules. In Punjab, the numbers of hazardous waste producing industries are 3023 which generate HW approximately 323 ton day-1 during 2008. Out of this 37 ton waste is disposable; 245 ton is recyclable while 41 ton waste is incinerable. It has been observed that the contribution of Indian Acrylics Ltd., Sangrur (Punjab) and Pasupati Acrylon Ltd., Muradabad (Uttar Pradesh) towards the generation of total HW in respective states is only 0.2 and 0.1 % respectively. Indian Acrylics Ltd. has its own incinerator while Pasupati Acrylon Ltd. supplies the HW to common treatment facility. These industries seem to obey HW (Management & Handling) Rules.
Ph.D
Keywords: Incineration; medical waste; waste management